2020
DOI: 10.1155/2020/9395629
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Leisure Participation Assessment Tool for the Elderly

Abstract: Objectives. This study is aimed at developing multidimensional leisure participation assessment tool for the elderly to achieve quantitative and qualitative assessment of leisure participation and leisure exploration. Methods. This study collected preliminary items through literature review, statistical office data, and survey of the elderly’s leisure activities and considered the list of leisure activities as assessment items by conducting a Delphi survey. Reliability was verified through internal consistency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Leisure activities are aimed at older adults' leisure, relaxation, pleasure, and development [ 24 ]. Studies have shown that reasonable leisure activities contribute to the physical and mental health of older adults and promote their family harmony [ 25 ]. Leisure activity can curb depression in older adults and promote longevity [ 22 ].…”
Section: Hypothesis and Frameworkmentioning
confidence: 99%
“…Leisure activities are aimed at older adults' leisure, relaxation, pleasure, and development [ 24 ]. Studies have shown that reasonable leisure activities contribute to the physical and mental health of older adults and promote their family harmony [ 25 ]. Leisure activity can curb depression in older adults and promote longevity [ 22 ].…”
Section: Hypothesis and Frameworkmentioning
confidence: 99%
“…Since then, there have been approximately 71 million confirmed cases and 1.6 million deaths worldwide [1]. The WHO officially declared COVID-19 a pandemic on 12 March 2020, making it the third pandemic following the 1968 Hongkong flu and the 2009 novel influenza A (H1N1). The symptoms of COVID-19 include fever, dry cough, and fatigue and this disease is currently known to be transmitted through droplets generated during coughing or sneezing, or through touching the eyes, nose, or mouth after coming in contact with a COVID-19-contaminated surface [2].…”
Section: Introductionmentioning
confidence: 99%
“…OTPF accounts for a large proportion of research in the field of occupational therapy. In a number of studies, including studies for occupation in mild Traumatic Brain Injury patients, studies for Instrumental Activities of Daily Living (IADL) in Parkinson patients, development of leisure participation evaluation tools for the elderly, and studies for activities and health of the elderly outside the home, OTPF can be seen as an important basis [10][11][12][13]. The Occupational Therapy Practice Framework 4th edition (OTPF-4) includes health management as one of the nine major occupational domains that is independent from all the other domains [14].…”
Section: Introductionmentioning
confidence: 99%
“…The health situation of the global pandemic due to COVID-19 hindered the physical contact of grandparents and grandchildren [7][8][9], a circumstance that shows the need to contribute with research that will once again promote intergenerational festive exchanges, and resume the impulse to acknowledge the grandparents as bearers of an extensive cultural background, although safely and healthily.…”
Section: Introductionmentioning
confidence: 99%